Intolerance of Uncertainty and Loneliness in Older Adults During the COVID-19 Pandemic - Parlapani, Eleni; Holeva, Vasiliki; Nikopoulou, Vasiliki A.; Sereslis, Konstantinos; Athanasiadou, Maria; Godosidis, Athanasios; Stephanou, Theano; Diakogiannis, Ioannis (Frontiers in Psychiatry, 2020)
Objective: The COVID-19 pandemic imposed a psychological burden on people worldwide, including fear and anxiety. Older adults are considered more vulnerable during public health emergency crises. Therefore, the aim of the present study was to investigate the psychological response of older adults during the acute phase of the pandemic in Greece. Method: This cross-sectional study was part of a larger three-day online survey. A total of 103 participants over the age of 60 fulfilled inclusion criteria. The survey included sociodemographic questions and six psychometric scales: the Fear of COVID-19 Scale (FCV-19S), the Brief Patient Health Questionnaire (PHQ-9) depression scale, the Generalized Anxiety Disorder scale (GAD-7), the Athens Insomnia Scale (AIS), the Intolerance of Uncertainty Scale (IUS-12), and the De Jong Gierveld Loneliness Scale (JGLS). Results: A significant proportion of the participants reported moderate to severe depressive symptoms (81.6%), moderate to severe anxiety symptoms (84.5%), as well as disrupted sleep (37.9%). Women reported significantly higher levels of COVID-19-related fear, more severe depressive symptoms and sleep disturbances, as well as higher levels of intolerance of uncertainty. Participants living alone showed higher levels of loneliness. Intolerance of uncertainty was shown to modulate levels of loneliness. Conclusions: During the quarantine, attention was promptly drawn upon the risks related with older people’s loneliness. Studies identifying factors that may contribute to loneliness during a public health emergency facilitate the implementation of supportive interventions. Preparedness to address and manage older people’s loneliness may limit this deleterious emotional response during the pandemic, as well as at the post-COVID-19 phase.